ENTANGLEMENT MEASURE AND MONOGAMY INEQUALITY IN QUDIT CONCURRENCE - Yanuwar, Edyharto
As a distinctive aspect of the quantum world, entanglement poses challenges in its measurement and quantification. This research focuses on entanglement in highdimensional quantum systems (qudits), emphasizing the measurement of entanglement and the monogamy inequality. Monogamy inequality states that quantum correlations cannot be freely shared, unlike classical correlations. This study utilizes concurrence as a measure of entanglement, which has proven effective in qubit systems. Although entanglement in qubits is widely understood, its extension to qudit systems remains challenging. In this study, the equivalence of concurrence definitions for qubits is examined and extended to qudits. Additionally, the monogamy inequality is explored with a novel measure that accommodates all possible states, including counterexamples that are already known, to understand the properties of entanglement. This approach is expected to enhance the understanding of entanglement in qudit systems and contribute to the broader advancement of quantum understanding.